Expression of Multiple Exogenous Insect Resistance and Salt Tolerance Genes in Populus nigra L. - Zhou, Xinglu; Dong, Yan; Zhang, Qi; Xiao, Dandan; Yang, Minsheng; Wang, Jinmao (Frontiers in Plant Science, 2020)
Four exogenous genes, Cry3A, Cry1Ac, mtlD, and BADH, were inserted into the p1870 vector to obtain polygenic transgenic Populus nigra L. with improved insect resistance and salt tolerance. During vector construction, different promoters were used for each gene, the AtADH 5′-UTR enhancer was added between the Cry1Ac promoter and the target gene, and the MAR structure was added at both ends of the vector. It was then successfully transferred into the genome of P. nigra by Agrobacterium-mediated leaf disk transformation, and a total of 28 transgenic lines were obtained by kanamycin screening. Five strains with the highest insect resistance were selected based on preliminary tests: Nos. 1, 7, 9, 12, and 17. PCR, fluorescence quantitative PCR, and enzyme-linked immunosorbent assays (ELISA) were used to detect the expression of exogenous genes and to analyze the Bt protein toxin levels in transgenic lines from June to October. PCR results showed that all four genes were successfully introduced into the five selected lines. Fluorescence quantitative PCR showed no significant differences in the transcript abundance of the four exogenous genes between different lines. A Bt protein toxin assay showed that the Cry3A protein toxin content was significantly higher than the Cry1Ac protein toxin content by approximately three orders of magnitude. Levels of the two toxins were negatively correlated. Over the course of the growing season, Cry1Ac content raised and varied between 0.46 ng·g−1 and 18.41 ng·g−1. Cry3A content decreased over the same time period and varied between 2642.75 ng·g−1 and 15775.22 ng·g−1. Indoor feeding insect experiments showed that the transgenic lines had high insect resistance, with mortality rates for 1–2-year-old Hyphantria cunea larvae reaching more than 80%, and mortality rates for Plagiodera versicolora larvae and nymphs reaching 100%. No. 17 and No. 12 lines had better insect resistance to Lepidoptera and Coleoptera pests. There was no clear improvement in salt tolerance of the transgenic lines, although comprehensive evaluation results of 11 salt tolerance indices showed that lines No. 17 and No. 7 had certain degrees of salt tolerance.